2015
DOI: 10.1002/anie.201508449
|View full text |Cite
|
Sign up to set email alerts
|

An Electrically Driven and Readable Molecular Monolayer Switch Based on a Solid Electrolyte

Abstract: The potential application of molecular switches as active elements in information storage has been demonstrated through numerous works. Importantly, such switching capabilities have also been reported for self-assembled monolayers (SAMs). SAMs of electroactive molecules have recently been exploited as electrochemical switches. Typically, the state of these switches could be read out through their optical and/or magnetic response. These output reading processes are difficult to integrate into devices, and furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…[48][49][50] The morphologyo fe thylenediamine-modifiedG Ow as further studied by both TEM (Figure S2 bi nt he Supporting Information) and SEM ( Figure S3). [56,57] Porphyrin-modifiedGO Chemical modificationo fg raphene with porphyrin can generate interesting donor/acceptor hybrid systems for energy conversion and storage, and optoelectronic devices. SEM measurements of ethylenediaminemodified GO in the solid state show some flake features.T he presence of nitrogen was also confirmed by means of energydispersive X-ray spectroscopy (EDX) mapping ( Figure S3 in the Supporting Information).…”
Section: Ethylenediamine-modified Gomentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50] The morphologyo fe thylenediamine-modifiedG Ow as further studied by both TEM (Figure S2 bi nt he Supporting Information) and SEM ( Figure S3). [56,57] Porphyrin-modifiedGO Chemical modificationo fg raphene with porphyrin can generate interesting donor/acceptor hybrid systems for energy conversion and storage, and optoelectronic devices. SEM measurements of ethylenediaminemodified GO in the solid state show some flake features.T he presence of nitrogen was also confirmed by means of energydispersive X-ray spectroscopy (EDX) mapping ( Figure S3 in the Supporting Information).…”
Section: Ethylenediamine-modified Gomentioning
confidence: 99%
“…[51][52][53][54][55] Conversely,f errocene is aw ell-known redoxactive molecule, which has been shown to represent as uitable buildingb lock for applications in sensing, electrochemically switchable devices and memories, and so forth. [56,57]…”
Section: Ethylenediamine-modified Gomentioning
confidence: 99%
“…[1] In particular, SAMs tailored with a redox active terminal group have arisen great interest because they can shed light into the mechanisms of the heterogeneous electron transfer as well as for the fabrication of electrochemical switchable systems. [2][3][4][5][6] For instance, SAMs based on ferrocene, [7,8] fullerene, [9] tetrathiafulvalene, [10] porphyrin, [11] and quinone [12][13][14][15] have been successfully exploited in a wide spectrum of applications including charge storage, cells guidance, protein grafting, and charge transport. Further, several groups have unambiguously demonstrated that inert [16,17] and redox-active SAMs [18][19][20][21] can be efficiently used to modify the surface energy when a voltage is applied to them.…”
Section: Introductionmentioning
confidence: 99%
“…The covalent graftingo ff unctional molecules on solid supports has been shown to be ap romising route to fabricate smarts witchable surfaces that respond to externals timuli (i.e., optical,e lectrical, chemical). [18][19][20][21][22] Accordingly,a nd motivated by the possibility to develop an ovel highlys ensitivee lectrochemicalp latform for PAHs determination, ah ybrid material based on as elf-assembled monolayer (SAM) of an aromatic carbonm olecule on indium tin oxide (ITO) ablet oi nteract with PAHs has been fabricated. Pyrene was used as ap robe recognition agento wing to its planar aromatic structure, whicha llows synergistic p-p interactions with PAHs.…”
mentioning
confidence: 99%